Qurʾanic Recitation in the Procession of Analyzing Seven Days of Death: The Case Study of Living Qurʾan-Hadith in Koto Padang Village - Mandala, Ican (Al-Bayān, 2025)
Differences in understanding and interpretation of the Qurʾan and Hadith have given birth to different religious practices. The variety of textual perceptions of the community presents the contextual uniqueness of religious traditions in the social environment. Among them is the practice of Ngetaih Qiraʾah (Qurʾan recitation) tradition for seven days in the process of tahlilan death in Koto Padang Village, Tanah Kampung District, Sungai Penuh City. Ngetaih Qiraʾah has become routine and mandatory in the implementation of tahlilan for the bereaved family. In fact, the family will feel awkward if they do not perform this tradition during the seven-day tahlilan. Family relatives and heirs will recite the Qurʾan for seven consecutive nights at the funeral home after isyaʾ, some families even invite Qoriʾ and Hafizh (memorization) Qurʾan. This research aims to reveal how the meaning of the Ngetaih Qiraʾah tradition as a form of birrul walidain practice. The type of method used is a qualitative method that is field research, with a living Qurʾan-Hadith approach. The process of collecting data by observation and interview. Data analysis is done through the stages of data condensation, data presentation, and conclusion drawing. This research found that the tradition of Ngetaih Qiraʾah is a phenomenon of living Qurʾan-Hadith practice. The meaning of this tradition is a form of awareness of birrul walidain, namely the devotion of a child to parents by reciting the Qurʾan as an effort to pray for people who have died. The meaning of birrul walidain is found in the procession of its implementation, the limited ability of reciting the Qurʾan of the heirs does not limit the devotion of children to parents. So that it encourages heirs to pray for parents through their financial capabilities. The practice of this tradition is the implementation of the hadith that human deeds are cut off after death, except for the prayers of pious children.